Pengembangan E-Modul dalam Meningkatkan Hasil Belajar pada Mata Pelajaran Ekonomi - Pajriah Pajriah; Ari Saptono; Aditya Pratama (CV. Ulil Albab Corp, 2024)
The development of e-modules was carried out to become a learning medium that can be used as a learning resource for students. The aim of this research is to determine the effect of using e-modules on learning outcomes in financial services institution material. This research is development research or Research and Development with the ADDIE development model. Data analysis used qualitative and quantitative descriptive analysis and unpaired t-test. The research subjects were one material expert, one language expert, one media expert, two panelists, and students. The research population was class X students of SMA Negeri 14 Jakarta. The sample used was non-random sampling using a deliberate sampling technique and class X-2 was obtained as the experimental class while the control class was class X-4. The results of this research include 1) the validation results of the e-module based on visual media using Canva are valid as shown by the material expert validation score of 83.75%, the media expert obtained a score of 94.5%, the linguist obtained a score of 94.3%, the panelists I was 92%, and panelist II obtained a score of 91% with all scores included in the